Assessment of surveillance activity for malaria control under national anti malaria programme in Yadgir district, Karnataka - Sunil, B. N.; Naresh Kumar, S. J. (International Journal Of Community Medicine And Public Health, 2018)
Background: This paper reports the findings of evaluation of National Anti-malaria programme (NAMP) conducted independently for Government of India in Yadgir district of Karnataka state in February 2011, by the Department of Community Medicine, Sri Devaraj Urs Medical College, Kolar. Methods: A community based cross-sectional study was conducted in Yadgir district. Multistage sampling was employed to select the study population. The head of the household and other members present in the household were interviewed and the data was recorded in a predesigned semi-structured questionnaire. The obtained data was entered in the MS excel sheet and analyzed for proportions. Results: Data was collected from 1026 eligible persons. Eight (0.77%) fever cases were distributed among study population. Among fever cases only two (25%) had taken chloroquine. Only one (12.5%) blood smear were taken from fever cases by health worker. Indoor residual spray was not done in any of households. Conclusions: Considering the poor blood smear collection, low intake of chloroquine among fever cases, there is a need to ensure the delivery of these services by health workers. Also steps should be taken to increase the awareness among health workers regarding second line treatment of malaria and insecticide impregnated bed nets.